Antioxidante no enzimático en jóvenes y adultos del Distrito El Porvenir - Carbajal Cabellos, Carol Eliana (2019)
In the present work, plasma levels of ascorbic acid were evaluated in young people and adults of the El Porvenir District, using a colorimetric method, which is measured at an absorbance of 760 nm. After processing 50 samples of blood serum it was obtained that 17% of young people present a low level of ascorbic acid and 83% present a normal level of ascorbic acid; in adults it was found that 11% had a low level of ascorbic acid and 89% had a normal level of ascorbic acid. In addition, by means of the Chi square test with a significance of <0.05 it was demonstrated and concluded that the age group does not influence, neither the sex in the level of plasma ascorbic acid.